TURBO GENERATOR SYSTEM IDENTIFICATION USING GENETIC ALGORITHM - R. Alsakini, Sahar; T. Alobaidi, Ahmed; J. Sultan, Ahmed (Journal of Engineering and Sustainable Development, 2016)
The turbogenerator is one of the mean important parts of the thermal power station, which is the most famous used as a generation power plant since the serving of electricity till now. The turbogenerator unit behavior is a non-linear and complicated system, for this causation, the identification models are used for the best and close optimization to have the highest and most accurate controller. In this paper, we will use the conjunction of data by intelligence techniques called "Genetic algorithm" to have the optimum behavior without using complex mathematical equations. The result we have from the genetic algorithm is showing the capability to reach the highest accuracy in system work identity, which are dependent on real data registered from no-load in the second unit of the Mussiab thermal power station.